2011
DOI: 10.1088/0953-2048/25/1/015008
|View full text |Cite
|
Sign up to set email alerts
|

Development of all chemical solution derived Ce0.9La0.1O2 −y/Gd2Zr2O7buffer layer stack for coated conductors: influence of the post-annealing process on surface crystallinity

Abstract: Preparation and characterization of a biaxially textured Gd 2 Zr 2 O 7 and Ce 0.9 La 0.1 O 2−y (CLO, cap)/Gd 2 Zr 2 O 7 (GZO, barrier) buffer layer stack by the metal-organic deposition route are reported. YBa 2 Cu 3 O 7−d (YBCO) superconductor films were deposited by the pulsed-laser deposition (PLD) technique to assess the efficiency of such a novel buffer layer stack. Biaxial texture quality and morphology of the buffer layers and the YBCO superconductor films were fully characterized. The surface crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 29 publications
0
20
2
Order By: Relevance
“…The CLO films and the YBCO-Ag films deposited by chemical solution routes were published previously [1,3]. Briefly, the CLO films were prepared by using a propionatesbased metal-organic solution, while the YBCO-Ag films were prepared by a novel sliver-assist fluorine-free MOD solution route.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CLO films and the YBCO-Ag films deposited by chemical solution routes were published previously [1,3]. Briefly, the CLO films were prepared by using a propionatesbased metal-organic solution, while the YBCO-Ag films were prepared by a novel sliver-assist fluorine-free MOD solution route.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we proposed and developed La doped CeO 2 (Ce 0.9 La 0.1 O 2-y , CLO) as a cap layer for an all-chemical derived coated conductors' configuration [1]. An YBCO layer prepared from low-fluorine MOD route was grown on a CLO buffered yttrium stabilized ZrO 2 (YSZ) template and exhibited high performance (>3 MA/cm 2 , self-field, 77 K) comparable with that of films grown on single crystalline LaAlO 3 by the similar route [2].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a buffer layer is crucial to obtain high critical current density (J c ). Various interlayers can act as a barrier against the two main defects mentioned above, and transfer the texture from the substrate up to the YBCO superconducting layer [5][6][7][8][9]. In recent years, chemical solution deposition (CSD) has proven to be more promising route than physical approaches to fabricate long coating lengths.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, buffer layers are absolutely necessary for coated conductor designs. Many buffer layers, including lanthanum zirconate (LZO) [2,3,4,5,6], cerium oxide (CeO 2 ) [7,8,9,10] and other lattice-matched buffer layers [11,12,13,14,15,16,17,18,19,20] which are prepared basically using solution-based methods have been used. These buffer layers should not only stop diffusion but also transfer the epitaxial texture of Ni-5% W substrate to the superconducting layer.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the high cost of multiple buffer layer depositions of LZO and CeO 2 , researchers have focused on preparing a single buffer layer with almost 0% lattice mismatch with YBCO and it was reported that the in-plane orientation of YBCO can be improved with these lattice matched buffer layers [11,12,13,14,15,16,17,18]. …”
Section: Introductionmentioning
confidence: 99%